The effect of equipment modification on the performance of novice junior cricket batters. Issue 21 (1st November 2020) - Dancy, Paul A. J.; Murphy, Colm P.
ABSTRACT: Equipment scaling has yielded better performance in children in comparison to using adult equipment. To better inform applied practice in junior sport, an investigation of additional equipment modifications designed to further simplify the task is required. This study, therefore, aims to determine the effect of increasing surface area of cricket equipment (bats and balls) on batting performance and technique. Forty-three children ( M age = 5.2, SD = 0.8 years) completed a cricket batting task in which they aimed to hit the ball through a target zone while using either regular-scaled, or modified bat and ball with an increased surface area. The number of bat-ball contacts was significantly higher when using the modified ( M = 13.81, SE = 0.42) compared to the regular-scaled ball ( M = 10.65, SE = 0.49). Batting performance measured as shots played through target areas was also significantly higher when using the modified ( M = 31.78, SE = 1.97) than the regular-scaled ball ( M = 28.85, SE = 2.27). More desirable technique was also observed when using the modified compared to the regular bat. Findings suggest that further modifications to regular-scaled equipment can enhance skill production.